Hubungan Antara Bahasa dan Kinerja Otak Manusia - Syifa Aien El Rahmah; Korin Kartika Putri; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Language is the result of complex cognitive processes processed by the brain, particularly in the left hemisphere through Broca's and Wernicke's areas, and other supporting areas. Coordination between brain regions determines language ability, while neurological disorders demonstrate the close relationship between language and brain function. This study employed a literature review method, reviewing various reliable scientific sources related to psycholinguistics and the relationship between language and brain function. Data were collected, critically analyzed, and systematically compiled to formulate concepts and theories that support the research focus. Language is a human cognitive ability that is highly dependent on brain function, particularly the cerebral cortex and the left hemisphere. Language processing involves Broca's and Wernicke's areas and the coordination of various brain regions. Language reflects thought, enabling communication, learning, and identity formation, with differences in brain function influencing variations in language ability. Language is a complex communication system regulated by the brain, particularly the left hemisphere's cerebral cortex through Broca's and Wernicke's areas, and the motor area. Although dominant in the left hemisphere, language processing requires cooperation between both hemispheres. Differences and disorders in brain development affect language ability and social cognition.